Jews and Anti-Jewish Rules in the Czech Codification of Church Law of 1349 - Lenka Šmídová Malárová (Journal on European History of Law)
The first codification of church law in the territory of the historically Czech lands, known as the provincial statutes of Ernst of Pardubice (Statuta provinicialia Arnesti), was issued in 1349, with validity for the entire Prague archdiocese. The Statute applied not only to the clerical and lay population, but also to Jews, for whom special rules and restrictions applied. The regulation of the legal and social life of the Jewish population is explicitly dealt with in three provisions (Articles 66-68), which mainly regulate the contact of Jews with Christians and their rights and obligations in public. Many of these prohibitions and regulations are based on papal decrees approved by the ecumenical councils, the text of which was reflected in the Decretals of Gregory IX and subsequently in the Mainz Statutes of Peter of Aspelt of 1310. The roots of these restrictions, however, in most cases go back to antiquity. This concerns, for example, the prohibition on hiring Christian nurses, midwives and servants; Jews were also not allowed to participate in public life, to build new synagogues or to improve existing ones. These measures were introduced by the Roman Emperor Theodosius II as part of the gradual process of Christianization of the Eastern Roman Empire. Although the legal provisions of the provincial statutes of Ernst of Pardubice imposed many restrictions on the Jews, this fact, on the other hand, was to some extent counterbalanced by protective provisions that prohibited laymen and Christian clergy from disturbing Jewish religious rites, destroying their graves, and arbitrarily punishing them without the existence of a relevant legal title.